DEVELOPMENT CHARACTERISTICS OF TOURISM AND RECREATION GEOGRAPHY AND THE FACTORS INFLUENCING IT - Baratova Dilnoza Nuritdinovna (American Journals, 2026)
This scientific article provides a comprehensive geographical analysis of tourism and recreation as complex spatial–socioeconomic phenomena and examines the key characteristics of their development as well as the natural, economic, social, cultural, infrastructural, and political factors influencing their territorial organization. Tourism and recreation geography is approached as an interdisciplinary field that studies the spatial distribution of tourism activities, the formation of recreational regions, and the interaction between natural landscapes, human activities, and economic systems. The study applies a systematic geographical framework to identify how tourism development varies across regions depending on resource availability, accessibility, demographic dynamics, and governance structures. The results demonstrate that tourism and recreation geography evolves unevenly in space and time, shaped not only by physical-geographical conditions but also by globalization processes, technological progress, urbanization, and environmental constraints. The findings highlight the growing importance of sustainable and spatially balanced tourism planning, emphasizing that uncontrolled tourism growth can lead to environmental degradation, social conflicts, and regional inequalities. The conclusions of the study contribute to regional planning, sustainable tourism strategies, and the development of tourism geography as a scientific discipline.
Keywords: Tourism geography, recreation geography, spatial development, tourism factors, regional planning, sustainable tourism.